Control Strategy of an Integrated Tunable Laser With a Single Intra-Cavity AMZI Filter - Martin Skenderas; Pablo Marin-Palomo; Spencer W. Jolly; Martin Virte (IEEE Photonics Journal)
Asymmetric Mach-Zehnder interferometers (AMZIs) can, in principle, enable continuous wavelength tuning of a laser when used as intra-cavity filters. Their simplicity and good compatibility with generic foundry platforms are major advantages. However, the difficulty to develop a well-defined and robust control strategy is an important drawback which restricts the use-cases of these tunable lasers. Here, we make an in-depth investigation of the tunability properties of a laser including a single-stage AMZI in its cavity. We find that due to imperfections of Electro-Optic Phase Modulators (EOPMs), the dependence of the phase variation with the applied voltage is not linear. Because integrated EOPMs cannot be individually calibrated, these nonlinearities prevent a precise and independent tuning of the phase and amplitude of the AMZI transfer function, and thus continuous tuning cannot be reliably achieved. To overcome this issue, we propose a refined control strategy which allows for semi-continuous tuning. With this approach, we demonstrate a piece-wise continuous tuning of the emission wavelength by taking advantage of the coupling between amplitude and phase in the AMZI response. With our refined control strategy, we achieve tuning of the emission wavelength over the full free spectral range (FSR) of the AMZI.